Investment Feasibility Of A Sand And Gravel Quarry Using The Benefit Cost Ratio Method A Case Study Of Pt. Arkatama Mining, Jayawijaya Regency, Indonesia - Obed Patiung; Mapuay Menasye Theo Afasedanya (Universitas Muhammadiyah Ponorogo, 2025)
The Wouma District in Jayawijaya Regency has significant potential for sirtu (sand and gravel) deposits, particularly along the Uwe River. PT. Arkatama Mining is one of the mining companies utilizing these resources for construction and mining activities. However, the economic feasibility and actual reserve quantity of sirtu have not been thoroughly studied. This research aims to analyze the economic feasibility of sirtu mining using the Benefit Cost Ratio (BCR) method. Data collection involved field measurements, interviews, and company document analysis. Results show that the mining area covers 4,320 m² with a sirtu resource volume of 38,880 m³. The BCR value obtained is 2.6, indicating that the project is economically feasible and profitable. The study recommends environmental monitoring and operational efficiency improvements to ensure sustainable mining practices.